Clearly Detectable, Kinetically Restricted Solid-Solid Phase Transition in cis-Ceramide Monolayers - Fanani, Maria Laura (2018)
Sphingosine [(2S,3R,4E)-2-amino-4-octadecene-1,3-diol] is the most common sphingoid base in mammals. Ceramides are N-acyl sphingosines. Numerous small variations on this canonical structure are known, including the 1-deoxy, the 4,5-dihydro, and many others. However, whenever there is a Δ4 double bond, it adopts the trans (or E) configuration. We synthesized a ceramide containing 4Z-sphingosine and palmitic acid (cis-pCer) and studied its behavior in the form of monolayers extended on an air-water interface. cis-pCer acted very differently from the trans isomer in that, upon lateral compression of the monolayer, a solid-solid transition was clearly observed at a mean molecular area ≤44 Å2·molecule-1, whose characteristics depended on the rate of compression. The solid-solid transition, as well as states of domain coexistence, could be imaged by atomic force microscopy and by Brewster-angle microscopy. Atomistic molecular dynamics simulations provided results compatible with the experimentally observed differences between the cis and trans isomers. The data can help in the exploration of other solid-solid transitions in lipids, both in vitro and in vivo, that have gone up to now undetected because of their less obvious change in surface properties along the transition, as compared to cis-pCer.